Comparison of biogenic amine concentrations in fermented fish with and without maize seedling extract - Kongkiattikajorn, Jirasak (Asia-Pacific Journal of Science and Technology, 2016)
Biogenic amines (BAs) are low molecular weight organic bases with aliphatic, aromatic, and heterocyclic structures. The formation of biogenic amines in food by the microbial decarboxylation of amino acids can result suffering allergic reactions, characterized by difficulty in breathing, itching, rash, vomiting, fever, and hypertension. Amine oxidase activity has become a particular interest to reduce biogenic amines concentration in food products such as Somfug or fermented fish. The aim of this study was to reduce biogenic amines accumulation during Somfug fermentation by maize seedling extract. Amine oxidase activity was measured by coupled reaction with peroxidase and guaiacol with putrescine as substrate at pH 7.5, 30 °C for 30 min. The amine oxidase activity of maize seedling extract was 27.54 U/ g fresh weight. The maize seedling extract of 10-24 ml was added in 100 g Somfug before fermentation. Amine oxidase activity of Somfug with maize seedling extract before fermentation was 5.50 U/ g Somfug. After 7 days of fermentation, total biogenic amines concentration was 83.04 % less in samples added with maize seedling extract, as compared to control samples. These results indicated that maize seedling extract with amines oxidase activity in Somfug fermentation was effective in reducing biogenic amines accumulation.